Antioxidant Activities of Muntingia calabura, Syzygium cumini, Ocimum basilicum, and Eleutherine bulbosa using DPPH Method - Ani Haerani; Anis Yohana Chaerunisa; Anas Subarnas (Indonesian Journal of Pharmaceutics, 2019)
Antioxidants are substances that can provide endogenous protection and exogenous oxidative stress by capturing free radicals. Many plants are efficacious as antioxidants, namely plants that contain polyphenols, especially flavonoids, so many are formulated as natural antioxidants. Plants such as Muntingia calabura, Syzygium cumini, Ocimum basilicum, and Eleutherine bulbosa contain polyphenol compounds, especially flavonoids which are efficacious as natural antioxidants. This research aimed to study antioxidant activity derived from some potential plants using the DPPH method by calculating the IC50 value of each plant extract. This research method starts from the determination process to prove the validity of the plants used, the extraction process using the maceration method with 70% ethanol solvent, then the antioxidant activity of extracts from each plant was carried out using the DPPH method. This research starts from the determination process to ensure the correctness of the plants used, then the extraction process is carried out using the maceration method with 70% ethanol solvent. After that the antioxidant activity was determined from the four plants using the DPPH method to see the strongest IC50 value among the four plants. IC50 is the concentration of the sample to inhibit 50% of free radicals. The results of IC50 values from ethanol extract of M. calabura leaves, Syzygium cumini leaves, Ocimum basilicum leaves and Eleutherine bulbosa bulbs, were 18.72; 63,84; 141.59 and 173.15 ppm. Ethanol extract of M. Calabura has a smaller IC50 value of 18.72 ppm which has a very strong and most powerful antioxidant from the ethanol extract of Syzygium cumini, Ocimum basilicum and Eleutherine bulbosa. Keywords : Antioxidant, Muntingia calabura, Syzygium cumini, Ocimum basilicum, Eleutherine bulbosa, DPPH Method